(untitled) (American Journal of Islam and Society, 2009)
Organized jointly by the Australian Intercultural Society, the Australian Catholic University, and Monash University together with the Gülen conference a few days earlier, this conference was devoted to a particularly important and pressing topic: the anti-Islam discourse slowly becoming a standard feature of western political competition and media coverage. As the topic is similarly a rather polarizing one, an event of high scholarly quality could not be taken for granted. However, this is just what organizers, speakers, and audience managed to achieve during this event, held during 18-19 July 2009 at Monash University in Melbourne. The phenomena subsumed under the term Islamophobia, their expressions, preconditions, and multiple roots and facets were discussed through different approaches in theoretical, descriptive, and analytical terms ...